2021
DOI: 10.1186/s12891-021-04501-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of smoking on outcomes following anterior cervical fusion-nonfusion hybrid surgery: a retrospective single-center cohort study

Abstract: Background There is mixed evidence for the impact of cigarette smoking on outcomes following anterior cervical surgery. It has been reported to have a negative impact on healing after multilevel anterior cervical discectomy and fusion, however, segmental mobility has been suggested to be superior in smokers who underwent one- or two-level cervical disc replacement. Hybrid surgery, including anterior cervical discectomy and fusion and cervical disc replacement, has emerged as an alternative proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 44 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…In addition, a significant difference in the early fusion process among current smokers, former smokers, and nonsmokers was detected for male patients, but no significant differences were founded at 1-year of follow-up. For female patients, statistical differences were found in both the early fusion process and the 1-year fusion rate ( 62 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a significant difference in the early fusion process among current smokers, former smokers, and nonsmokers was detected for male patients, but no significant differences were founded at 1-year of follow-up. For female patients, statistical differences were found in both the early fusion process and the 1-year fusion rate ( 62 ).…”
Section: Resultsmentioning
confidence: 99%
“…43 Patients who are current smokers show reduced rates of fusion postoperation compared with nonsmokers. [44][45][46] One study showed pseudarthrosis 1 to 2 years postsurgery in 40% of smokers vs 8% in nonsmokers. 44 The current study results show no impact of known risk factors on fusion rate or patient-reported outcomes when treated with PEMF.…”
Section: Discussionmentioning
confidence: 99%
“…This meta-analysis showed that patients who smoked were at higher risk for fusion failure. The combined OR of 8 studies [32,36,38,41,44,46,48,49] was 1.57 (95% CI, 1.11 to 2.21; I 2 = 0.0%) (Fig 3). The trim-and-fill method was used to assess the robustness of the results, and we did not find potentially missing studies (S6 Table ).…”
Section: Patient-related Risk Factorsmentioning
confidence: 99%